Photon Pairs from Resonant Metasurfaces - Santiago-Cruz, Tomás; Fedotova, Anna; Sultanov, Vitaliy; Weissflog, Maximilian A.; Arslan, Dennis; Younesi, Mohammadreza; Pertsch, Thomas; Staude, Isabelle; Setzpfandt, Frank; Chekhova, Maria (Nano Letters, 2021)
All-dielectric optical metasurfaces are a workhorse in nano-optics, because of both their ability to manipulate light in different degrees of freedom and their excellent performance at light frequency conversion. Here, we demonstrate first-time generation of photon pairs via spontaneous parametric-down conversion in lithium niobate quantum optical metasurfaces with electric and magnetic Mie-like resonances at various wavelengths. By engineering the quantum optical metasurface, we tailor the photon-pair spectrum in a controlled way. Within a narrow bandwidth around the resonance, the rate of pair production is enhanced up to 2 orders of magnitude, compared to an unpatterned film of the same thickness and material. These results enable flat-optics sources of entangled photons - a new promising platform for quantum optics experiments.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Mie-type resonances; nonlinear metasurfaces; photon-pair generation; quantum optics; spontaneous parametric down-conversion